Taxonomy and ontogeny of the Lituitida (Cephalopoda) from Orthoceratite Limestone erratics (Middle Ordovician) - Aubrechtová, Martina; Korn, Dieter (European Journal of Taxonomy, 2022)
Ordovician ectocochleate cephalopods of the order Lituitida Starobogatov, 1983, mainly from erratics of the Orthoceratite Limestone embedded in Pleistocene glacio-fluvial sediments in Germany, Poland and the Kaliningrad Region of Russia are revised. In total, seven genera (Rhynchorthoceras, Ancistroceras, Angelinoceras, Holmiceras, Lituites, Trilacinoceras, Cyclolituites) and 28 species are identified. Eleven species are newly described: Rhynchorthoceras kranepuhlense sp. nov., R. rugium sp. nov., Holmiceras havelense sp. nov., Lituites baculus sp. nov., L. bottkei sp. nov., L. clavis sp. nov., L. dewitzi sp. nov., L. kruegeri sp. nov., L. nebeni sp. nov., Trilacinoceras filix sp. nov. and T. knoefleri sp. nov. The concept of several taxa described in the 19th century, including the ambiguous species L. lituus de Montfort, 1808 and L. perfectus Wahlenberg, 1818, is refined. Neotypes are proposed for the latter two species.